The Difference Between Playing Games With and Without the Computer: A Preliminary View. - Antonietti, Alessandro; Mellone, Rosa (Journal of Psychology, 2003)
The authors address the question of whether associations between video games and cognitive and metacognitive variables depend either on the features of the computer or on the content of the game that the computer allows one to play. An experiment to separate these two kinds of effects was carried out by using a traditional version and a computer-supported version of Pegopolis, a solitaire game. The two versions were exactly the same except that they were played by moving pieces either on a real board or on a virtual computer-presented board. The performance levels and strategies followed during the game by the 40 undergraduates who took part in the experiment were not significantly different in the real and virtual conditions. None of the participants transferred playing strategies or practice from one version of the game to the other. Scores were not affected by gender or by the studies pursued by participants, the habit of playing games in the traditional manner or playing video games, or intelligence. Retrospective reports did not support differences in the subjective experience between the two versions. Results showed that video games, when they do not make much use of the computer's special features, produce effects because of the situations they simulate rather than because of features of the computer itself. Reprinted by permission of the publisher.